Optimal Packetization of Fine Granularity Scalability Codestreams for Error-Prone Channels - Zhu, Bin Benjamin; Yang, Yang; Chen, Chang Wen; Li, Shipeng (IEEE Int. Conf. Image Processing 2005, 2005)
An optimal source-channel packetization scheme for MPEG-4 Fine Granularity Scalability (FGS) codestreams is proposed in this paper. The channel is modeled with a uniform error distribution to the enhancement layer transmission. A cost function that models the error expansion for a MPEG-4 FGS stream is derived, and then used in the optimal packetization problem subject to the same overhead as the conventional packetization scheme. An efficient scheme to find the optimal solution is described, which takes time similar to encoding an MPEG-4 FGS codestream. Experiments show that our scheme has up to 1.96 dB gain over the conventional packetization scheme.